1985
DOI: 10.1007/bf00257289
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal alterations in heart and liver of mice treated with doxorubicin

Abstract: This study was carried out to evaluate the influence of long-term treatment with doxorubicin (DXR) (4 mg/kg IV for 5 weeks) on heart and liver lysosomes of mice. We evaluated the variations in both total and "sedimentable" enzyme activity of cathepsin D, which is the major endopeptidase of myocites and probably involved in physiologic and pathologic degradation of actomyosin and mitochondria, and that of acid phosphatase, which is more prominent in interstitial cells. Our results show that marked changes occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In fact, an early literature reported lysosome changes in cardiomyocytes, in terms of both numbers and morphology, induced by doxorubicin 1, 49 . It has been reported that doxorubicin also increases lysosomal membrane leakage 50 , although the changes seemed to be modest. Our data, for the first time, show that doxorubicin perturbs lysosomal function via inhibition of its luminal acidity.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, an early literature reported lysosome changes in cardiomyocytes, in terms of both numbers and morphology, induced by doxorubicin 1, 49 . It has been reported that doxorubicin also increases lysosomal membrane leakage 50 , although the changes seemed to be modest. Our data, for the first time, show that doxorubicin perturbs lysosomal function via inhibition of its luminal acidity.…”
Section: Discussionmentioning
confidence: 84%
“…A further paper gives supplementary information on the phenomena to be observed in aminoglycoside nephropathy of lysosomal origin (Roels et al 1984). The publication of Gebbia et al (1985) reports the effect of doxorubicin on the lysosomes of the heart and liver. One of the most recent substance-relevant publications is concerned with the effect of carcinogenic drugs on lysosomes (Bradley et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…After long-term ADR treatment in mice, changes in lysosomal enzyme activity have been reported for cathepsin D in the heart, and to a lesser extent in the liver [27]. In vitro stud ies revealed a certain accumulation o f ADR in the lysosomal compartment o f fibroblasts [28].…”
Section: Discussionmentioning
confidence: 99%